NecroX‐5 suppresses IgE/Ag‐stimulated anaphylaxis and mast cell activation by regulating the SHP‐1‐Syk signaling module. Issue 2 (23rd November 2015) - Li, X.; Kwon, O.; Kim, D. Y.; Taketomi, Y.; Murakami, M.; Chang, H. W.
Abstract: Background: IgE/Ag‐stimulated mast cells release various pro‐allergic inflammatory mediators, including histamine, eicosanoids, and pro‐inflammatory cytokines. NecroX‐5, a cell permeable necrosis inhibitor, showed cytoprotective effects in both in vitro and in vivo models. However, the anti‐allergic effect of NecroX‐5 has not yet been investigated. The aims of this study were to evaluate the anti‐allergic activity of NecroX‐5 in vivo and to investigate the underlying mechanism in vitro . Methods: The anti‐allergic activity of NecroX‐5 was evaluated in vitro using bone marrow‐derived mast cells (BMMCs) and IgE receptor‐bearing RBL‐2H3 or KU812 cells and in vivo using a mouse model of passive anaphylaxis. The levels of histamine, eicosanoids (PGD2 and LTC4 ), tumor necrosis factor‐α (TNF‐α), and interleukin‐6 (IL‐6) were measured using enzyme immunoassay kits. The mechanism underlying the action of NecroX‐5 was investigated using immunoblotting, immunoprecipitation, and gene knockdown techniques. Results: NecroX‐5 markedly inhibited mast cell degranulation and the synthesis of eicosanoids, TNF‐α, and IL‐6 by suppressing the activation of Syk, LAT, phospholipase Cγ1, MAP kinases, the Akt/NF‐κB pathway, and intracellular Ca 2+ mobilization via the activation of phosphatase SHP‐1. Oral administration of NecroX‐5 effectively suppressed mast cell‐dependent passive cutaneous and systemic anaphylactic reactions in a dose‐dependent manner. Conclusions: NecroX‐5 might be a potential candidate for the development of a novel anti‐allergic agent that suppresses IgE‐dependent mast cells signaling.